REVITALISASI NILAI KARAKTER DALAM PERIBAHASA DOLABILOLO: KAJIAN ETNOPEDAGOGI MASYARAKAT TIDORE - Nurbaya, Nurbaya; Ati, Sarmina (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
This study discusses the efforts to revitalize character values ​​in the Dolabilolo proverbs that have developed in Tidore society through an ethnopedagogical approach. Dolabilolo as a form of oral tradition contains moral values ​​that have the potential to be used as a source of character education based on local culture. The study used a descriptive qualitative approach with interview, observation, and documentation techniques. The results of the study show that Dolabilolo contains religious values, honesty, responsibility, hard work, cooperation, tolerance, trustworthiness, and social solidarity. Through an ethnopedagogical approach, these values ​​can be integrated into the education system to strengthen students' character and maintain local cultural identity. This study shows that local proverbs are not just a legacy, but a meaningful and contextual foundation for education..